EFEKTIVITAS KEBIJAKAN REHABILITASI TERHADAP ARTIS KORBAN PENYALAHGUNAAN NARKOTIKA BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Ahmad Zuhri; Erdianto Erdianto; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Drugs are substances or drugs derived from plants or non-plants, bothsynthetic and semi-synthetic, which can cause a decrease or change inconsciousness, loss of feeling, reduce to disappearance of pain, and can causedependence which is differentiated into groups as attached in the this law. LawNo. 35 of 2009 also states that those who are obliged to carry out medicalrehabilitation and social rehabilitation are not only narcotics addicts. Crime is anact whose perpetrators can be subject to criminal penalties. Narcotics addicts andvictims of Narcotics abuse must undergo medical rehabilitation and socialrehabilitation. The duty of law is to protect the interests of society. Legalprotection is all efforts to fulfill rights and provide assistance to give witnessesand victims a sense of security, legal protection for victims of crime as part ofcommunity protection, can be realized in various forms, such as throughrestitution, compensation, medical services, and legal assistance. Criminal lawpolicy or "penal policy" is a science as well as an art which ultimately has apractical objective to enable positive legal regulations to be better formulated andto provide guidance not only to legislators, but also to the courts that implementlaws and also to the organizers or implementation of court decisions.This research is a normative research by taking an approach to legaltheory, namely the theory of legal protection and the theory of criminal lawpolicy. Using secondary data by collecting data from library research (libraryresearch).From the results of the study it can be seen that the effectiveness of therehabilitation policy for artists who are victims of narcotics abuse has not beenable to change the bad habits of the perpetrators. Therefore, it is necessary tochange the rules in accordance with the times. Which can protect humanresources for the continuity of the nation, state and religion.Keywords: Effectiveness -Criminal-Narcotics-Abuse-drugs